Ilmu Al-Jarh Wa At-Ta’dil dalam Hadis: Studi Komparatif Metodologi Ibnu Hajar Al-Asqalani dan Ibnu Hatim Ar-Razi - Ilham, Ilham Syamsul; Labib, Muhammad Alfreda Daib Insan; Anisa , Farida Nur (Tasamuh: Jurnal Studi Islam, 2024)
This paper wants to examine the methodology used by Ibn Hatim Ar-Razi and Ibn Hajar Al-Asqalani in applying jarh wa ta'dil, with the aim of comparing the two methods used by the two scholars in applying jarh wa ta'dil. The research method in this paper uses qualitative research. The primary sources in this research are books of hadith science, books and scientific articles and some relevant previous research. Data analysis in this paper uses the method of description, comparison, and historical continuity methods. The results of this study are that the method used by Ibn Hatim Ar-Razi and Ibn Hajar Al-Asqalani tends to have similarities in men-jarh and men-ta'dil, even though the two of them do not live in the same period. Ibn Hatim Ar-Razi and Ibn Hajar Al-Asqalani tend to refer more to pre-existing texts, rely on the views of previous critical scholars, and accept the manuscripts of al-Jarh wa at-Ta'dil as true without much further evaluation.